2017
DOI: 10.1016/j.biocon.2017.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Tropical secondary forest regeneration conserves high levels of avian phylogenetic diversity

Abstract: Secondary forests are promoted as having pivotal roles in reversing the tropical extinction crisis. While secondary forests recover carbon and species over time, a key question is whether phylogenetic diversity—the total evolutionary history across all species within a community—also recovers. Conserving phylogenetic diversity protects unique phenotypic and ecological traits, and benefits ecosystem functioning and stability. We examined the extent to which avian phylogenetic diversity recovers in secondary for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 51 publications
7
44
0
Order By: Relevance
“…After correcting the correlation between species richness and PD (sesPD) and FD (sesFD), SFs had greater phylogenetic and functional dispersion than that found in PFs (Figure e,i). Higher sesPD in SFs thus suggests an increase of PD due to shifts in species composition towards, on average, less related species via losses of phylogenetically related species and/or gains of phylogenetically distant species, regardless of species richness (Edwards et al, ). The higher sesFD in SFs indicates lower levels of functional redundancy than that observed for PFs (Laliberté et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After correcting the correlation between species richness and PD (sesPD) and FD (sesFD), SFs had greater phylogenetic and functional dispersion than that found in PFs (Figure e,i). Higher sesPD in SFs thus suggests an increase of PD due to shifts in species composition towards, on average, less related species via losses of phylogenetically related species and/or gains of phylogenetically distant species, regardless of species richness (Edwards et al, ). The higher sesFD in SFs indicates lower levels of functional redundancy than that observed for PFs (Laliberté et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, multiple taxa recovered high TD in the Brazilian Amazon (Barlow et al, 2007). Additionally, Edwards, Massam, Haugaasen, and Gilroy (2017) found high recovery of PD for bird communities in the tropical Andes, while Lohbeck et al (2012) found high recovery of FD for tree communities in Mexico.…”
Section: Biodiversity Recoverymentioning
confidence: 94%
“…One study found that the null model was the best-fitting model in two of four cases (Major, Buxton, Schacter, Conners, & Jones, 2017), suggesting little support for the ecological hypotheses of interest. Several papers examined the match between observed and fitted values for an averaged model (Edwards, Massam, Haugaasen, & Gilroy, 2017;Mitchell, Bakker, Vincent, & Davies, 2017), while another undertook cross-validation on a model-averaged result (Cavada et al, 2017). The other 64 papers did not evaluate model goodness-of-fit in an absolute sense.…”
Section: The Best Models Frequently Are Not Assessedmentioning
confidence: 99%
“…Although ecologists and conservationists have focused on deforestation, extensive areas of the tropics are naturally regenerated forest and their importance for biodiversity has not been fully explored (Achard et al 2002, Aide et al 2013, Chazdon et al 2016, Reid et al 2018. While most secondary forest studies have focused on vegetation, recent studies have analysed the recovery patterns of vertebrates during secondary forest succession (Andrade and Rubio-Torgler 1994, Medellin and Equihua 1998, Blake and Loiselle 2001, Crouzeilles et al 2017, or have evaluated the functional (Sayer et al 2017) and phylogenetic diversity (Edwards et al 2017) of vertebrates in tropical secondary forest. Understanding these dynamics is essential for generating management plans and conservation strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is important to account for the variation in the recovery of different functional groups (Cadotte et al 2011). In secondary forest, the recovery of bird forest specialists can take more than 100 years (Sayer et al 2017), while bird phylogenetic recovery can occur in only 30 years (Edwards et al 2017). The inconclusive and contrasting patterns of vertebrate diversity recovery is due to relatively few studies, grouping species with different natural histories such as forest specialists and habitat generalists, not controlling for different habitats, biomes or biotic and abiotic factors (e.g.…”
Section: Introductionmentioning
confidence: 99%